Analisis Higiene dan Sanitasi terhadap Keberadaan Bakteri Coliform pada Minuman Es Serbuk Instan - Siti Julaikhah; Riyan Ningsih; Ervinda Yuliatin (Poltekkes Kemenkes Semarang, 2026)
The problem of microbiological contamination in snack drinks is still a public health issue, especially in instant powdered ice drinks, which are at risk of contamination because they go through various stages of handling, such as water mixing, the use of ice cubes, contact with equipment, and direct contact by sellers. This study aims to analyze the relationship between personal hygiene of handlers and sanitation facilities to Coliform bacterial contamination in instant powdered ice drinks at Segiri Market, Samarinda City. The study used a quantitative approach with a cross-sectional design. A sample of 21 traders was selected using the total sampling technique. Data was collected through observation using the Environmental Health Inspection (EHI), as well as Coliform examination using the Most Probable Number (MPN) method. Data analysis was carried out univariate and bivariate using Fisher's Exact Test (α=0.05). The results showed that 61.9% of handlers had unqualified personal hygiene, and 47.6% had unqualified sanitation facilities, and 85.7% of samples of Coliform-contaminated beverages exceeded the threshold (0 MPN/100 ml). The results of the statistical test showed that there was a significant relationship between personal hygiene (p=0.042) and Coliform contamination, but there was no relationship between sanitation facilities (p=1,000) and Coliform contamination. It was concluded that the personal hygiene of handlers plays a role in the microbiological quality of beverages, so increased education and supervision are needed to reduce the risk of contamination.